[tex]\bf 12~~,~~\stackrel{12-5}{7}~~,~~\stackrel{7-5}{2}~~,~~\stackrel{2-5}{-3}~~,~~\stackrel{-3-5}{-8}~~...[/tex]
so, as you can see, the "common difference" is -5, namely to get the next term we simply "add" -5 to the current one, and we know the first term is 12, ok, so,
[tex]\bf n^{th}\textit{ term of an arithmetic sequence}
\\\\
a_n=a_1+(n-1)d\qquad
\begin{cases}
n=n^{th}\ term\\
a_1=\textit{first term's value}\\
d=\textit{common difference}\\
----------\\
d=-5\\
a_1=12\\
n=33
\end{cases}
\\\\\\
a_{33}=12+(33-1)(-5)\implies a_{33}=12+(32)(-5)
\\\\\\
a_{33}=12-160\implies a_{33}=-148[/tex]